Applicability of a jurisdiction agreement to a claim of damages by infringement of Article 102 TFEU: the Apple Sales International case (C-595/17) - Calvo Caravaca, Alfonso-Luis; Suderow, Julia (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Private enforcement of Competition Law is not limited to cartel damage claims based on infringements of art. 101 TFUE. Follow on and Stand alone actions against the abuse of dominance sanctioned by art. 102 TFUE are also included. They are actions derived from unilateral conducts where jurisdiction agreements play an important role. In the ruling Apple Sales, the ECJ solves certain doubts about the scope of this type of clauses but its answer generates new questions that will be dealt in future disputes. The will of the parties as well as the proportionality will still be the basis of the exclusivity of the forum.
Keywords: antitrust damages actions; stand-alone actions; follow-on actions; jurisdiction agreements; arbitration; jurisdiction; damages (Torts); Antitrust Law; European Competition Law; European Union